An increased risk of non‐melanoma skin cancer during TNF‐inhibitor treatment in psoriasis patients compared to rheumatoid arthritis patients probably relates to disease‐related factors. (17th September 2014) - van Lümig, P.P.M.; Menting, S.P.; van den Reek, J.M.P.A.; Spuls, P.I.; van Riel, P.L.C.M.; van de Kerkhof, P.C.M.; Fransen, J.; Kievit, W.; de Jong, E.M.G.J.
Abstract: Background: Concerns exist about a risk of non‐melanoma skin cancer (NMSC) in psoriasis patients and rheumatoid arthritis (RA) patients treated with TNF‐inhibitors. However, current data also show that in some psoriasis patients, NMSC is diagnosed relatively short after the start of TNF‐inhibitors, which suggests that these NMSC can be explained by previous therapies instead of by TNF‐inhibitor therapy. Objective: To investigate whether there was a difference in time until first NMSC and the rate of NMSC between psoriasis and RA patients on TNF‐inhibitors. Methods: Time until first NMSC and the rate of NMSC were compared between psoriasis and RA patients from the same region treated with TNF‐inhibitors and followed up for at least one year in prospective cohort studies, by using Cox regression and Poisson regression. Both analyses were corrected for confounders (age, gender, disease duration, prior NMSC, duration of anti‐TNF and other systemic therapies). Results: The NMSC risk was significantly higher in the psoriasis group [fully adjusted HR 6.0 (1.6–22.4 95%CI)] with a shorter time until first NMSC in psoriasis compared to RA. By Poisson regression, psoriasis patients had a 5.5 (2.2–13.4 95%CI) higher rate of NMSC. Conclusion: The time until first NMSC was significantly shorter and the rate of NMSC was significantly higher in psoriasis compared with RA. This indicates that disease‐related factors like phototherapy may be important contributing factors to NMSC diagnosed in psoriasis patients treated with TNF‐inhibitors.